Aging, Osteo-Sarcopenia, and Musculoskeletal Mechano-Transduction - Leser, Jenna M.; Harriot, Anicca; Buck, Heather V.; Ward, Christopher W.; Stains, Joseph P. (Frontiers in Rehabilitation Sciences, 2021)
The decline in the mass and function of bone and muscle is an inevitable consequence of healthy aging with early onset and accelerated decline in those with chronic disease. Termed osteo-sarcopenia, this condition predisposes the decreased activity, falls, low-energy fractures and increased risk of co-morbid disease that leads to musculoskeletal frailty. The biology of osteo-sarcopenia is most understood in the context of systemic neuro-endocrine and immune/inflammatory alterations that drive inflammation, oxidative stress, reduced autophagy, and cellular senescence in the bone and muscle. Here we integrate these concepts to our growing understanding of how bone and muscle senses, responds and adapts to mechanical load. We propose that age-related alterations in cytoskeletal mechanics alter load-sensing and mechano-transduction in bone osteocytes and muscle fibers which underscores osteo-sarcopenia. Lastly, we examine the evidence for exercise as an effective countermeasure to osteo-sarcopenia.